The environmental effects caused by solid waste industries clothing in polo fashion of Maringá-PR - Alencar, Jose Luciano Sobreira de; Fiorelli, Mariana Natale; Simoni, Julio Henrique; Neto, Generoso de Angelis; Link, Paula Piva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article provides some observations about the importance of sustainability to the apparel sector and also the problems caused by the generation of solid residues in the apparel industries. Initially this paper discusses sustainability, presenting some data related to the apparel manufacturing sector in the city of Maringá; Later it discusses the issues and legal guidelines related to the management of solid residues and the importance ofproper actions and good practices in this process, preventing possible impacts to the population, the urban system and even for the environment. It was noted the need of integration between people, entrepreneurs and government to ensure the compliance with local, state and federal regulations, aiming better quality of life and respect for the environment.